Effectiveness Of Raspberry Seed Oil In Natural Sunscreen Formulation Using Different Percentage Of Zinc Oxide - Sharif, Norazreen; Ahmad, Muhammad Amir Faris; Mohamad Yazid, Nur Hawanie Syahira; Yahya, Nurul Nabilah (Multidisciplinary Applied Research and Innovation, 2021)
A natural sunscreen is made from natural ingredients that are used to replace the common sunscreen that uses multiple chemicals that has negative effects such as allergic reaction and free radicals besides can absorb the harmful Ultraviolet (UV) rays before it penetrates to the skin. Then, this project to solve the issues related to skin disease caused of harmful UV rays such as sunburn and skin cancer which is directly influenced by a climate change need to be done. The objectives of this research are to study the sunscreen effect of natural ingredients that contains red raspberry seed oil and other organic oil with aloe vera, to develop a minimum amount of zinc oxide of the sunscreen that has higher than 30 Sun Protection Factor (SPF) and a high UV-A Protection, to characterize the functional group of the sunscreen product by using Fourier Transform Infrared Spectroscopy (FTIR). The natural ingredients and zinc oxide 20%, 10%, 15%, 5%, and 0% are mixed into the sunscreen formulation to absorb UV-B and UV-A. The results from the UV-Vis and FTIR are to identify the absorbance and functional groups that obtained in the product which shows the product having a broad-spectrum UV protection and 44.67 SPF plus having Methyl Mercapto as an active functional group in the product. In conclusion, the best formulation of natural sunscreen consists of 100% natural ingredients like red raspberry seed oil with aloe vera, virgin coconut oil, olive oil, and a 5% amount of zinc oxide to replace the chemical compound.